Form of register in the trader's word traditional floating market in Banjarmasin city - Dana Aswadi; Erni Susilawati (English, 2018)
This paper aims at discussing the form of a word register among traditional traders Floating Market in Banjarmasin. Language has various variations with various linguistic phenomena, especially with respect to the word registers. The phenomenon of language in Floating Market in Banjarmasin city is very interesting. The approach used is qualitative Deskrptif approach. Descriptive approach aims to collect, classify, and analyze the data so as to obtain the form of registers among traders in the Floating Market Banjarmasin City. In the data collection, researchers used several techniques, namely observation techniques, docomentation techniques, recording techniques, and techniques refer to note. The form of a register is a word found, in the form of verbs, nouns, and adjectives.